DIFFERENTIATION BETWEEN PORCINE AND BOVINE GELATIN IN CAPSULE SHELLS BASED ON AMINO ACID PROFILES AND PRINCIPAL COMPONENT ANALYSIS - Widyaninggar, Amalia; ., Triwahyudi; Triyana, Kuwat; Rohman, Abdul (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Gelatin used for capsule shells can be derived from porcine origin. Some religion like Islam prohibited their followers to consume any products containing porcine derivatives including porcine gelatin in the products. Consequently, some rapid and reliable techniques are continuously developed for detection of porcine gelatin in some pharmaceutical products like capsule shells. The aim of this study was to evaluate the possibility to use amino acid profile in combination with chemometrics of principal component analysis for detection and classification between gelatin in capsule derived from porcine and bovine. Based on score plot of first principal components (PC1) and second principal components (PC2), porcine and bovine gelatins in capsule could be apparently distinguished.Key words: bovine gelatin; porcine gelatin; amino acid profile; principal component analysis